Blockchain technology: Energy efficiency and ethical compliance - Fernando, Yudi; Rubakanthan, Saravannan (Penerbit Universiti Malaysia Pahang, 2021)
Blockchain technology has the ability to disrupt almost every industry due to its ability to create a decentralized tamper-proof ledger network and carry out transactions without the need of a trusted third party intermediary. One of the major drawback of blockchain technology is the energy consumption surrounding its application. The problem has been discussed extensively, with proposals focusing on strengthening its consensus protocol and also integrating renewable energy sources to minimize its carbon footprint. To boost adaptability of blockchain in all sectors, the technology itself needs to look for less energy-intensive alternatives to boost its ethical and industrial compliance. As the energy sector is currently undergoing a revamp from its age-long one-way power network towards a decentralized grid system with distributed generation and storage. Adoption of blockchain technology must work hand in hand with the energy industry in order to make itself energy efficient and competitive in the long term.